Legal Protection of Workers in Indonesia's Gig Economy for Digital Ecosystems: Challenges and Solutions in the Digital Labor Law Framework - Badru Jaman, Ujang; Pertiwi, Endah; Zibele Nodangala, Norless; Manga Mokofe, William; Abdul Malik, Muhamad Rizki (Mawaddah: Jurnal Hukum Keluarga Islam, 2025)
Fast and immense growth of Indonesia's gig economy using digital platforms raises many questions regarding challenges to Indonesia's prevailing legal frameworks about labor law. Gig workers are easily vulnerable on account of their unclear employment status, social security, gaps in the regulations of digital ecology, and access to dispute resolution mechanisms. The current study will explore the legal protection for gig workers in Indonesia from a juridical point of view, pinpoint lacking policies and their socio-economic impacts, and advance practicable solutions: the reclassification of employment, obligatory contributions to social security by platforms, heightened regulatory oversight, and bespoke dispute resolution systems, drawing from a review of global best practices and theoretical frameworks. The findings highlight through legislation how urgent these much-needed reforms are in treating gig workers equitably and furthering sustainable growth in Indonesia's digital economy, given that gig work is constantly changing.